An Empirical Investigation into the Listing Performance of Indonesian IPOs - Gupta, Ambrish (Indian Journal of Research in Capital Markets, 2020)
This paper has been written with the objectives of providing insights into the demographic characteristics of 2018 IPO market in Indonesia, and investigating and analyzing the listing performance of IPOs floated during 2018 in the country so as to expand the existing knowledge base on the subject and enable the various stakeholders associated with IPOs to take more informed decisions and thus contribute to better development of the IPO market in Indonesia. Analysis of listing performance of 2018 IPOs assumed further significance since in the history of the Indonesian capital market, the year 2018 witnessed the largest number of IPOs, highest number of shares issued, and highest amount of funds raised. It is really remarkable that out of 57 IPOs, only 4 returned listing loss ; whereas, 53 returned gains. Thus, a very high 93% of IPOs were underpriced. Only 7% of them were overpriced. All the gains and losses put together, the investors earned a very high return of 26% on the listing day itself.